Pelatihan Penulisan Cerita Anak Bergambar Berbasis E-Book: Transformasi Literasi Digital - Muhammad Iqbal; Widya Widya; Riza Andriani; M Rafli Al Thoriq Mustafa; Faisal Faisal (Universitas PGRI Semarang, 2024)
Program